Emodin reverses leukemia multidrug resistance by competitive inhibition and downregulation of P-glycoprotein. - Hongping Min; Miaomiao Niu; Weilin Zhang; Jia Yan; Jiachang Li; Xiying Tan; Bo Li; Mengxiang Su; Bin Di; Fang Yan (PLoS ONE, 2017)
Development of multidrug resistance (MDR) is a continuous clinical challenge partially due to the overexpression of P-glycoprotein (P-gp) for chronic myelogenous leukemia (CML) patients. Herein, we evaluated the inhibitory potency of emodin, a natural anthraquinone derivative isolated from Rheum palmatum L, on P-gp in P-gp positive K562/ADM cells. Competition experiments combined with molecular docking analysis were utilized to investigate the binding modes between emodin and binding sites of P-gp. Emodin reversed adriamycin resistance in K562/ADM cells accompanied with the decrease of P-gp protein expression, further increasing the uptake of rhodamine123 in both K562/ADM and Caco-2 cells, indicating the inhibition of P-gp efflux function. Moreover, when incubated with emodin under different conditions where P-gp was inhibited, K562/ADM cells displayed increasing intracellular uptake of emodin, suggesting that emodin may be the potential substrate of P-gp. Importantly, rhodamine 123 could increase the Kintrinsic (Ki) value of emodin linearly, whereas, verapamil could not, implying that emodin competitively bound to the R site of P-gp and noncompetition existed between emodin and verapamil at the M site, in a good accordance with the results of molecular docking that emodin bound to the R site of P-gp with higher affinity. Based on our results, we suggest that emodin might be used to modulate P-gp function and expression.